Rancang Bangun Web Profil Pada Prodi Filsafat Universitas Pembangun Pancabudi - aulia, izzmi; Muhammad Muttaqin; Muhammad Iqbal (CV. Hawari, 2025)
The use of information technology in the world of education is very important to increase the effectiveness of academic services and the promotion of study programs. This research aims to design and build a website-based information system in the Philosophy Study Program, Panca Budi Development University. The method used is software development with an object-oriented analysis and design (OOAD) approach, starting from needs analysis, design, and implementation to system testing. The results of the study show that the developed website is able to provide profile information, news, activities, galleries, and contacts online, making it easier to access information for students, lecturers, prospective students, and the general public. This website also functions as an effective digital promotional medium and supports the digitization of academic services in the study program environment. System testing shows a high level of user satisfaction with the ease of access and completeness of information.